CREATION OF A WATER LEVEL MONITORING STATION FOR FISH CULTIVATION IN PETUK LITI VILLAGE USING GLOBAL SYSTEM FOR MOBILE COMMUNICATIONS (GSM) - Trissan, Whendy; Tarita Aprilani Sitinjak; Samuel Layang; Wiratno Y Sigin; Petrisly Perkasa; Topan Eka Putra; Gagas Wira Syahputra; Nathanael Yanuar Kristianto (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2024)
Fish farming is a promising business alternative, especially in rural areas such as Petuk Liti Village. With the potential of existing natural resources, good management is needed so that cultivation results can be optimal (Iskandar & Muslih, 2022). One important aspect of fish farming is controlling water quality, especially water level, which affects fish health and growth (Rahmadani, 2021).However, the challenge faced by fish farmers is the difficulty of monitoring water levels in real-time, so that decisions are often made that are not appropriate, which can be detrimental to cultivation results. Therefore, this PKM activity aims to develop a water level monitoring station based on remote camera technology (GSM) which is implemented in Petuk Liti Village, Pulang Pisau Regency, Central Kalimantan.The monitoring station designed in this research consists of several main components, including a monitoring camera, a water level sensor, and a GSM module which functions to transmit data.The output target of this service is expected to make a significant contribution in increasing the efficiency and effectiveness of fish farming in Petuk Liti Village. With a monitoring station, farmers will be quicker and more accurate in taking the necessary actions, so that cultivation results can be optimal.